2011
DOI: 10.1111/j.1365-2591.2011.01976.x
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of calcium hydroxide‐based intracanal medicaments against Enterococcus faecalis

Abstract: In this laboratory study using extracted teeth all calcium hydroxide-based medicaments were able to significantly reduce the CFU mL(-1) values of E. faecalis in the root canal system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
47
1
8

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(58 citation statements)
references
References 34 publications
(96 reference statements)
2
47
1
8
Order By: Relevance
“…13,14,15,19 Calcium hydroxide paste has strong biological and antimicrobial properties due to its highly alkaline pH 8 and is considered the gold standard intracanal medication for treating endodontic infections. However, calcium hydroxide has disadvantages, such as its low potential against E. faecalis, 3,26 which can survive in dentin tubules for long periods in the presence of the antimicrobial agent. 18,26 Thus, in this study, the brown propolis extracts were mixed with calcium hydroxide to observe a possible improvement of the calcium hydroxide paste against E. faecalis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…13,14,15,19 Calcium hydroxide paste has strong biological and antimicrobial properties due to its highly alkaline pH 8 and is considered the gold standard intracanal medication for treating endodontic infections. However, calcium hydroxide has disadvantages, such as its low potential against E. faecalis, 3,26 which can survive in dentin tubules for long periods in the presence of the antimicrobial agent. 18,26 Thus, in this study, the brown propolis extracts were mixed with calcium hydroxide to observe a possible improvement of the calcium hydroxide paste against E. faecalis.…”
Section: Discussionmentioning
confidence: 99%
“…However, calcium hydroxide has disadvantages, such as its low potential against E. faecalis, 3,26 which can survive in dentin tubules for long periods in the presence of the antimicrobial agent. 18,26 Thus, in this study, the brown propolis extracts were mixed with calcium hydroxide to observe a possible improvement of the calcium hydroxide paste against E. faecalis.…”
Section: Discussionmentioning
confidence: 99%
“…The results of the present study demonstrated that the association with CHX favored the antibacterial activity of CH against E. faecalis. These results may be related to the reduction in E. faecalis adhesion to dentin 19,20 , and its sensitivity to CHX 10,17,21,22 .…”
Section: Discussionmentioning
confidence: 99%
“…faecalis biofilm induced in root canals for 21 days, allowed the propagation of the microorganisms into dentinal tubules and root canal system. Therefore, the methodology allowed evaluation of the antibacterial effect of the medications against the microorganisms into root canal systems 10 . The evaluated medications were effective in eliminating E. faecalis from main canal, as demonstrated in the post-medication sample (S2).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation